2023
DOI: 10.3390/su15064995
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Digital Economy on Technological Innovation: Evidence from Manufacturing Enterprises in China

Abstract: Digital economy is a key breakthrough in the new round of the industrial revolution, and technological innovation is the key to economic growth and wealth creation by enterprises. The influence of the digital economy on the innovation of manufacturing enterprises is directly related to solving the problem of inadequate development. Therefore, it is of great theoretical value and practical significance to study the influence of the digital economy on enterprise technological innovation. Taking Chinese manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Through the Moran index and panel regression models, Wang Qiong et al studied the effect of the digital economy on enterprise technological innovation from 2016 to 2020 using a sample of Chinese manufacturing enterprises. They came to the conclusion that the digital economy has a double promotional effect on enterprise technological innovation [18].…”
Section: Literature Review 21 Related Literature On the Digital Economymentioning
confidence: 99%
“…Through the Moran index and panel regression models, Wang Qiong et al studied the effect of the digital economy on enterprise technological innovation from 2016 to 2020 using a sample of Chinese manufacturing enterprises. They came to the conclusion that the digital economy has a double promotional effect on enterprise technological innovation [18].…”
Section: Literature Review 21 Related Literature On the Digital Economymentioning
confidence: 99%
“…At present, some research remains at the theoretical analysis level without quantifying the impact of technological innovation on total employment. However, the empirical results in this paper show that green technology innovation plays a significant intermediary role between the digital economy and the scale of enterprise labor demand, with the main pathway being that the digital economy promotes green technology innovation within companies [22], and enterprise green technology innovation further increases the labor demand scale [34]. Song's research found that progress in environmentally biased technologies can facilitate the supply and demand of regional labor [60], while Yang Xue et al demonstrated that technological innovation did not result in significant substitution pressure to Japan's overall labor employment [61], both of which aligned with the conclusions of this study.…”
Section: Discussionmentioning
confidence: 70%
“…This transmission mechanism aligns with the mechanism of mediation effects. Mainly, the digital economy has shown a significant ability to promote green technology innovation within enterprises [21,22]. Concurrently, green technology innovation can influence the scale of enterprise labor demand by reducing production costs, expanding business operations, increasing the likelihood of engaging in new production activities, and generating demands for research and development management.…”
Section: The Results Of the Mediation Effect Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From a macro perspective, the positive effects of the DE on innovation were proven by analyzing data from 29 countries [4], Chinese provinces [2,3], and Chinese prefecture-level cities [5]. From a micro perspective, by conducting empirical research on the relevant data of Chinese A-share listed companies and Chinese manufacturing listed companies, the significant promotion effect of the DE on enterprise innovation has been confirmed [6][7][8][9]. It follows that the DE is a driving force for innovation development of macro-and micro-agents.…”
Section: Introductionmentioning
confidence: 99%